The universal dimension of work in the light of selected socio-economic transformations - Ryszard Gerlach (Institute of Social Affairs of the Pedagogical University of Cracow, 2023)
The work of man is a subject that falls within the interest of various scientific disciplines. In this article, it is considered from the perspective of pedagogy, specifi cally one of the sub-disciplines of labour pedagogy. It is a universal concept, constituting an important research problem in this scientific sub-discipline. The purpose of the discussions in this study is to show the relevance of the universal dimension of human labour in light of the socio-economic transformations that are occurring extremely rapidly, especially in recent years. This was done using a literature analysis, mainly of the latest research. Scientific research and theoretical analyses on the topic of labour have not been frequently undertaken by labour pedagogues lately. In analysing the literature on this subject, the directions and character of permanent changes in labour were emphasised. Recognising that labour still is and will be a universal value, at least in the foreseeable future, the necessity of adapting education, mainly vocational, to anticipated changes was stressed. Therefore, this remains a current area of research and analysis concerning human labour and education for labour, as well as in the course of labour. Uniwersalny wymiar pracy w świetle wybranych przeobrażeń społeczno-gospodarczych Praca człowieka to zagadnienie będące w obszarze zainteresowań różnych dyscyplin naukowych. W niniejszym artykule rozpatrywana jest w ujęciu pedagogiki, a w szczególności jednej z subdyscyplin pedagogiki pracy. Jest to pojęcie uniwersalne, stanowiące ważny problem badawczy tej subdyscypliny naukowej. Celem rozważań w tym opracowaniu jest ukazanie aktualności uniwersalnego wymiaru pracy człowieka w świetle przeobrażeń społeczno-gospodarczych zachodzących niezwykle szybko, szczególnie w ostatnich latach. Zrobiono to wykorzystując analizę literatury, głównie najnowszej. Badania naukowe i analizy teoretyczne na temat pracy nie były ostatnio zbyt często podejmowane przez pedagogów pracy. Analizując literaturę na ten temat podkreślano kierunki i charakter permanentnych zmian w pracy. Uznając, że praca nadal jest i będzie wartością uniwersalną, przynajmniej w dającej się przewidzieć przyszłości, podkreślono konieczność dostosowywania edukacji, głównie zawodowej do antycypowanych zmian. Jest to więc nadal aktualny obszar badań i analiz dotyczących pracy człowieka oraz edukacji dla pracy, a także w toku pracy.